Conservation status of Crax globulosa in the National Reserve Pacaya Samiria, Loreto, Perú - Yahuarcani, Antonio (2008)
Since May to July 2006 the state of conservation of the Crax globulosa Spix, 1825 was studied in the buffer zone of the National Reserve Pacaya Samiria. In the villages of Vista Alegre and San Pedro de Maypuco the information was gathered through workshops, surveys, interviews and lectures that provided information on the perception and knowledge of local people about the species. Censuses and observations were conducted in the community of Vista Alegre. Crax globulosa during periods of wet season prefers the upper forest and small areas of land locally known as the highest restingas; in dry season occupies the entire space of the restingas, preferring closed forests of lakes locally known as cochas and pipes. 22 groups and 50 individuals were observed, and its density was estimate in 3-4 individuals/km2. This work confirms the presence of C. globulosa, and its distribution in the lower Ucayali.